Tetrabenzanthanthrenes by mitigation of rearrangements in the planarization of ortho-phenylene hexamers1. Issue 33 (28th April 2015) - He, Jian; Mathew, Sanyo; Kinney, Zacharias J.; Warrell, Rachel M.; Molina, James S.; Hartley, C. Scott
<x xml:space="preserve">Abstract</x> Stepwise planarization of an ortho-phenylene hexamer demonstrates that otherwise inaccessible graphenes may be achievable from substrates with polycyclic repeat units.